Suppression of Presymptomatic Oxidative Stress and Inflammation in Neurodegeneration by Grape-Derived Polyphenols - Herman, Francis; Westfall, Susan; Brathwaite, Justin; Pasinetti, Giulio M. (Frontiers in Pharmacology, 2018)
Neurodegenerative disorders constitute a group of multifaceted conditions characterized by the progressive loss of neurons and synaptic connections due to a combination of specific genetic predispositions and stochastic stressors. The neuropathologies observed in both Alzheimer’s and Parkinson’s disease are in part attributed to compounding intrinsic and extrinsic environmental stressors, which we propose may be limited by the administration of specific grape derived phytochemicals and their metabolized derivatives, specifically polyphenols isolated from grape botanicals. Current therapies for neurodegenerative disorders are limited as they solely target the final disease pathologies including behavioral changes, cognitive deficits, proteinopathies and neuronal loss; however, this strategy is not a sustainable approach towards managing disease onset or progression. This review discusses the application of grape derived polyphenols as an adjunctive treatment paradigm for the prevention of neuropathologies associated with Alzheimer’s disease, Parkinson’s disease and Chronic Traumatic Encephalopathy by simultaneously ameliorating two stochastic stressors that facilitate their disease pathologies: inflammation and oxidative stress. The biophysical attributes of grape-derived polyphenols buffer against redox potential dependent peripheral and neuroinflammation and down regulate the activation of inflammasomes in microglia and astrocytes, which could provide a novel mechanism through which grape-derived polyphenols simultaneously suppress risk factors across pathologically distinct neurodegenerative conditions. This paradigm therefore offers a prophylactic mode, not feasible through current pharmacological agents, to target activity dependent risk factors for neurodegenerative disorders that manifest over an individual’s lifetime.